Reviews (Blackfriars, 1934)
Book reviewed in this article: Religion and Communism. By Julius F. Hecker, Ph.D. The Truth and Error of Communism. By H. G. Wood, M.A. Communism and the Alternative. By A. J. Penty.s The Church and the Jews in the Thirteenth Century. By Solomon Grayzel. Italy and the Reformation to 1550. By G. K. Brown, M.A., Ph.D. The USE of Poetry and the use of criticism. By T. S. Eliot. Now I See. By Arnold Lunn. Gates of Hell. By Erik R. v. Kuhnelt-Leddihn. Whistles of Silver and other Stories. By Helen Parry Eden. CINEMA